2019
DOI: 10.1111/sms.13485
|View full text |Cite
|
Sign up to set email alerts
|

Acute high‐intensity football games can improve children's inhibitory control and neurophysiological measures of attention

Abstract: Recent studies suggest that a single bout of exercise can lead to transient performance improvements in specific cognitive domains in children. However, more knowledge is needed to determine the key exercise characteristics for obtaining these effects and how they translate into real‐world settings. In the present study, we investigate how small‐sided football games of either high‐ or moderate‐intensity affect measures of inhibitory control in a school setting. Eighty‐one children (mean age 11.8, 48 boys) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 49 publications
1
21
0
3
Order By: Relevance
“…The present study also provides novel evidence regarding the effects of Football on subsequent cognitive function (particularly working memory) in adolescents, with only one previous studying investigating the acute effects of Football [ 24 ]. The majority of previous work in adolescents has used traditional forms of exercise; such as continuous running [ 6 , 7 , 19 , 20 ], walking [ 8 ] and cycling [ 9 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The present study also provides novel evidence regarding the effects of Football on subsequent cognitive function (particularly working memory) in adolescents, with only one previous studying investigating the acute effects of Football [ 24 ]. The majority of previous work in adolescents has used traditional forms of exercise; such as continuous running [ 6 , 7 , 19 , 20 ], walking [ 8 ] and cycling [ 9 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 87%
“…Football was chosen because it is high-intensity and intermittent in nature and thus replicates the activity patterns typically observed in this population [ 21 ]; as well as being an enjoyable and popular form of games-based activity for young people [ 46 ] and thus has ecological validity. A duration of 60 min was selected to advance on previous work examining the effects of 60 min of Basketball [ 16 ], whereas research utilising Football protocols is typically shorter in duration (20 min) [ 24 ]. An experienced Football coach delivered the sessions to groups of 10 participants, on outdoor facilities at the respective schools.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies in healthy children showed physical activity-induced acute effects on neurophysiological functioning. Results indicated improved neurophysiological functioning during rest ( Mierau et al, 2014 ) and goal-directed behavior ( Chen et al, 2016 ; Mierau et al, 2014 ; Wollseiffen et al, 2018 ), greater allocation of attentional resources during task performance ( Chu et al, 2017 ; Hillman et al, 2009 ; Lind et al, 2019 ; St Louis Deschenes et al, 2015 ) and improved conflict processing ( Chu et al, 2017 ). Three of the seven studies reported accompanying beneficial effects on measures of cognitive performance ( Chen et al, 2016 ; Hillman et al, 2009 ; Lind et al, 2019 ) or academic functioning ( Hillman et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%